Gender Representation in EFL Textbooks in Indonesia - Fatmawati Fatmawati; Leonardus Par; Yosefina Rosdiana Su; Ely Heldydiana Selamat; Indawati Nur Mahir (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2022)
Analysing gender issues in the teaching materials in the textbook is crucial as students' way of perceiving gender in their daily lives might be shaped by what they have learned at school. This research concerns analysing how gender representation in two EFL textbooks utilized in Indonesian secondary schools, Pathway to English for SMA/MA grade, later called textbook 1 in this study and Forward an English Course for Vocational School Students Grade VII, which was later called textbook 2. Both were published by Erlangga. The theory of personal characters proposed by (Brugeilles and Sylvie, 2009) was used as the basis theory in this study. Employing mixed-method research approaches, the researchers analysed how visuals in both textbooks portrayed gender representation by focusing on the frequency of pictures of male and female characters, occupations and activities. The study reveals that the two books show an imbalance of gender representation in all three aspects. Gender bias, especially for female occupations and activities, is apparent in the two textbooks. This study suggests that EFL teachers evaluate their textbooks to advocate for gender equality in the classroom.